Regulatory T cells: potential in organ transplantation. - Wood, K; Luo, S; Akl, A (2004)
Active regulation or suppression of donor reactive cells is emerging as a key mechanism for inducing and maintaining unresponsiveness to donor alloantigens. Accumulating evidence suggests that a balance between immunoregulation and deletion of donor alloantigen reactive T cells can provide effective control of immune responsiveness after organ or cell transplantation. In many settings, immunoregulatory activity is enriched in CD4+ T cells that express high levels of CD25, and common mechanisms appear to be responsible for the activity of regulatory T cells in both transplantation and the control of reactivity to self-antigens.